Report From the Society of Thoracic Surgeons National Database Workforce: Clarifying the Definition of Operative Mortality. (January 2013) - Overman, David M.; Jacobs, Jeffrey P.; Prager, Richard L.; Wright, Cameron D.; Clarke, David R.; Pasquali, Sara K.; O'Brien, Sean M.; Dokholyan, Rachel S.; Meehan, Paul; McDonald, Donna E.; Jacobs, Marshall L.; Mavroudis, Constantine; et al.
Several distinct definitions of postoperative death have been used in various quality reporting programs. Some have defined postoperative mortality as the occurrence of death after a surgical procedure when the patient dies while still in the hospital, while others have considered all deaths occurring within a predetermined, standardized time interval after surgery to be postoperative mortality. While mortality data are still collected and reported using both these individual definitions, the Society of Thoracic Surgeons (STS) believes that either approach alone may be inadequate. Accordingly, the STS prefers a more encompassing metric, Operative Mortality. Operative Mortality is defined in all STS databases as (1) all deaths, regardless of cause, occurring during the hospitalization in which the operation was performed, even if after 30 days (including patients transferred to other acute care facilities); and (2) all deaths, regardless of cause, occurring after discharge from the hospital, but before the end of the 30th postoperative day. This article provides clarification for some uncommon but important scenarios in which the correct application of this definition may be challenging.